John L. Esposito, Tamara Sonn, And John O. Voll (2016). Islam And Democracy After The Arab Spring. Oxford: Oxford University Press. 306 Pages. ISBN: 978-0-19514798-8 - Saidin, Mohd Irwan Syazli (Journal of Al-Tamaddun, 2022)
This book discusses the dynamics of the relationship between Islam as a religious and political teaching with democracy in the context of the effects of the Arab Spring and the subsequent events after it. The authors, who are considered to be “titans” in the field of democracy and Islam, started the book by saying “Many western observers were shocked when Arabs began open rebellions against their governments in December 2010” and this seem to point out not only the unpredictability of the uprisings, but also to the inaccuracy behind several of the most accepted assumptions about politics and governance in the Arab world. The chapters of the book discuss the experiences of political transition in general and how democratisation works in particular through the examples of seven different countries, namely Turkey, Iran, Pakistan, Indonesia, Senegal, Tunisia and Egypt.